Physicochemical Principles of Synthesis and Modification of Unsaturated Polyester-Polyvinyl Chloride Composites and the Properties of Materials Derived from Them - Diana Katruk; Volodymyr Levytskyi; Ulyana Khromyak; Volodymyr Moravskyi; Andrii Masyuk (International Journal of Polymer Science)
The influence of the polymeric modifier of polyvinyl chloride on the structuring of unsaturated polyester resins has been investigated. It is established that the introduction of 2–5 parts by weight of polyvinyl chloride into a polyester composite accelerates the process of gelation and shortens the time of microgelation of the polyester. The influence of polyvinyl chloride on the structure coefficient, surface hardness, and strength of adhesive bonds and technological shrinkage of modified polyester composites has been revealed.